FAKTOR- FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMBELI PRODUK YAMAHA CV.MAHKOTA MOTOR (PANAM) PEKANBARU - ', Nurhatini; ', Suarman; ', Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine the factors that influence consumer behavior in making purchasing decisions Yamaha brand motorcycles of CV. Mahkota Motor (Panam) Pekanbaru. The method used is desriptive quantitative research.The population sample as many as 95 people and 75 people with the sampling method that is accidental sampling. Variables used in this research is the independent variable (independent variable) including : (X1) cultural factor, (X2) social factor, (X3) personal factor, (X4) psychological factor. Analysis of the data used is descriptive analysis and factor analysis. From the results, it can be concluded that : 1. These four factor can influence the consumer decision, 2. The most dominant factor with a value of 53,694% variance that cultural factor. CV. Mahkota Motor (Panam) Pekanbaru conduct a series of activities to maintain, attract and increase customer loyalty so that in can bring in as many costumers as.Keywords : cultural factors, social factors, personal factors, psychological factors, and the consumer decision.